Phase Ⅰ and phase Ⅱ metabolic studies of Citrus flavonoids based on electrochemical simulation and in vitro methods by EC-Q-TOF/MS and HPLC-Q-TOF/MS. (30th June 2022) - Yue, Zi-Xuan; Gu, Yu-Xin; Yan, Tian-Ci; Liu, Fang-Ming; Cao, Jun; Ye, Li-Hong
Highlights: EC/Q-TOF/MS is used for analyzing metabolic transformations. Phase I and phase II simulated metabolism of citrus flavonoids were studied. In vitro microsomes analysis confirmed the possibility of electrochemical simulation of metabolism. This developed method is efficient, simple and fast. Abstract: The oxidation products and metabolic pathways of five Citrus flavonoids were studied by online electrochemical/quadrupole time-of-flight mass spectrometry (EC/Q-TOF/MS). The simulated oxidation metabolism of target compounds in phase I and phase Ⅱ was carried out at boron-doped diamond (BDD) working electrode. The results obtained by EC-MS were compared with the conventional metabolism of rats and humans reported in previous literatures. In addition, the method of incubating the target compounds with rat liver microsomes in vitro was established, the target compounds and their metabolites were analyzed by high performance liquid chromatography coupled mass spectrometry. The structures of the metabolites were determined by accurate mass measurements and previous in vivo metabolite results. The results showed that the electrochemical oxidation metabolites were consistent with the results of in vitro incubation of liver microsomes, and also with the results reported in other literatures. As a consequence, EC/Q-TOF/MS is a promising and effective tool for studying metabolic transformation of different complex food components.